Pengaruh Lingkungan Bisnis, Strategi Operasi, dan Teknologi sebagai Variabel Pemoderasi terhadap Kinerja Operasional Perusahaan: Studi pada Perusahaan Manufaktur di Indonesia - Anatan, Lina (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2006)
Expanding global competition, rapidly changing market and technology, increasing complexity and uncertainty are creating new competitive environment where manufacturing firm must adopt and implement sophisticated operational strategy, technology, and imprwemenl techniques f they want to stoy competitive. To be successful in this globally competitive and rapidly changing environment, organization must formulate strategic plan that are consistent with their investment in and use of technology and consider environment lask as precursor variable that causally related to stralegic c'hoice. This research was conducted to irwestigate the relationship amongsl business envit'onmenl, operational slrqleg/, and .firm pedormance of manufacturing.firms in Indonesia. This study also investigotes the moderaling role of technologt (both hard and soft technologXt) on the strategt and perfurmance relalionship. Data are collected through mailed questionnsire (525 questionnqires) and direct suruey to 25 tirms. The total questionnaires are sent to 550 CEOs manufacturing firm in Indonesia. A hundred and six responses are returned yielding response rate 19.27ok.